Two Artists, Solo Show, Vicky Pericleous – Vasilis Zografos The unsettling event of an enigma (to be forever, but never to have been*), curated by Maria Stathi - Pericleous, Vicky; Zografos, Vasilis (My University, 2025)
Art Seen is delighted to present Vicky Pericleous and Vasilis Zografos duo solo exhibition. "The exhibition unfolds through a subversive and associative dialogue toward a visual investigation, which primarily choreographs the unseen, intermediary space. That is, the dialectical space between the two, the space between the works, as well as the one that potentially arises through the viewers’ interpretations. The site-specific installation that emerges in space through a set of spatiotemporal expansions, folds and compactions, - a product of visual performativities and speculations- could, at last, be inscribed or re-thought as the after-sound, or even as the –interactive- echo of one or multiple events. The title of the exhibition recalls Man Ray's work L’Enigme d’Isidore Ducasse (1920), and the subtitle refers to the eponymous phrase in Jorge Luis Borges' poem The Enigmas from the collection Jorge Luis Borges, Selected Poems, 1923-1967 (1972). This collaborative installation, intending to involve the unseen as existent and the intangible as active in order to process and extend the visible and the perceptible, is primarily a political act.
Keywords: Arts; Solo Show/Exhibition; site-specific installation; dialectical space; spatiotemporal expansions, folds and compactions; Topos; visual performativities and speculations